Attachment to Church Congregation: Contributions to Well-Being over and above Social Support. Issue 4 (December 2017) - Freeze, Tracy A.
Over the last three decades, research has established a strong link between attachment and well-being as well as social support and well-being. Past research found that attachment to church congregation predicted well-being over and above that predicted by attachment to God. However, it is unknown if attachment to church congregation predicts well-being over and above that predicted by social support. Therefore, the purpose of this study was to determine if attachment to church congregation could explain a portion of the variance in negative affect, positive affect, satisfaction with life, and daily spiritual experiences, beyond that explained by religious social support and perceived social support. The data from 201 participants indicated that religious social support, perceived social support, and attachment to church congregation each predicted different aspects of well-being. Only negative affect was predicted by attachment to church congregation beyond that predicted by social support. More research is needed to better understand the relationship between attachment to church congregation, social support, and well-being.